2013
DOI: 10.1016/j.jpedsurg.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Primary payer status is significantly associated with postoperative mortality, morbidity, and hospital resource utilization in pediatric surgical patients within the United States

Abstract: Purpose Current healthcare reform efforts have highlighted the potential impact of insurance status on patient outcomes. The influence of primary payer status (PPS) within the pediatric surgical patient population remains unknown. The purpose of this study was to examine risk-adjusted associations between PPS and postoperative morbidity, mortality, and resource utilization in pediatric surgical patients within the United States. Methods A weighted total of 153,333 pediatric surgical patients were evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 26 publications
9
49
0
Order By: Relevance
“…Third, the present study provides an association between race and gender to the primary outcomes of mortality and morbidity in addition to hospital length of stay and total charge and does not support conclusive causality within these relationships. Fourth, this study does not directly examine the effect of payer status on risk-adjusted outcomes as this has recently been demonstrated within pediatric surgery[6]. Fifth, interinstitutional transfers cannot be tracked through patient identifiers, introducing the potential confounding effect of multiple entries for a single patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the present study provides an association between race and gender to the primary outcomes of mortality and morbidity in addition to hospital length of stay and total charge and does not support conclusive causality within these relationships. Fourth, this study does not directly examine the effect of payer status on risk-adjusted outcomes as this has recently been demonstrated within pediatric surgery[6]. Fifth, interinstitutional transfers cannot be tracked through patient identifiers, introducing the potential confounding effect of multiple entries for a single patient.…”
Section: Discussionmentioning
confidence: 99%
“…Procedural codes as classified by the ICD-9 procedure coding system were matched to diagnoses and included: small bowel resection, air contrast enema, appendectomy, decortication, pyloromyotomy, diaphragm repair, and colonic resection[5]. The selected operations modeled prior analyses on primary payer status and were chosen to achieve a representative spectrum of morbidity and mortality for both infant and childhood illness [6]. Patients were stratified according to gender and race for comparison: white, black, Hispanic, Asian or Pacific Islander, Native American, and other.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we found no association with survival rates in teaching or nonteaching hospitals. Other studies have found the KID database to be an excellent source for examining how outcomes are affected by socioeconomic and payer status [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the KID database remains an excellent source of outcomes information for the pediatric population, especially given its large sample size and information about socioeconomic, epidemiologic, and payer status. Several retrospective reviews of pediatric surgical conditions have used this database to analyze outcomes [11,12,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Although acquiring health insurance may play a role in reducing disparities across socioeconomic groups, [10][11][12] expanding health insurance access does not guarantee that patients receive high quality care. [9,13,14] The Hospital Value Based Purchasing Program, implemented by the Centers for Medicare and Medicaid Services (CMS) as part of the Affordable Care Act (ACA), links healthcare quality with healthcare reimbursements to improve the quality of care received by all patients, regardless of socioeconomic or insurance status.…”
Section: Introductionmentioning
confidence: 99%